Characterization of the boron profile and coordination in altered glass layers by EEL spectroscopy. (February 2021) - Aréna, H.; Podor, R.; Brau, H.-P.; Nelayah, J.; Godon, N.; Cabié, M.; Garcès, E.; Mansas, C.; Rébiscoul, D.
Highlights: EELS is used to study the boron concentration profile in altered glass layers. Boron concentration profiles are S-shaped with a thickness of about 40 nm. The trivalent boron proportion decreases along the boron concentration profile. These results suggest a higher bonding strength for B IV bonds than that of B III bonds. Abstract: Electron energy-loss spectroscopy was used to characterize the boron profile and its coordination (B III and B IV ), along the complex alteration layer of glass samples altered for 511 days at 50 °C in solution containing FeCl2, MgCl2 and/or CaCl2 . To reach this goal, the impact of both TEM operating conditions and sample preparation on the determination of the boron coordination was first studied using mineralogical and pristine glasses reference samples. Then, the boron concentration profiles were characterized in the glass alteration layer. These profiles were found to be S-shaped with a thickness around forty nanometers. The proportion of B III was found to decrease with the boron total concentration (from the pristine glass to the gel layer), which suggests a higher bonding strength for B IV bonds than that of B III bonds under the alteration conditions. These findings are of tremendous interest to advance further in the understanding of glass alteration mechanisms.